Analysis of subsurface defects occurrence in abrasion resistant Creusabro steel after WEDM including the study of morphology and surface topography. Issue 2 (3rd March 2020) - Mouralova, K.; Prokes, T.; Benes, L.; Sliwkova, P.
Abstract: Unconventional wire electrical discharge machining technology is an indispensable part of the production of many industrial devices. Material separation takes place at very high local temperatures, and therefore, some undesirable surface and sub-surface defects are formed. Not only the occurrence of defects but also the quality of the machined surface is very important for the end customer, so it is necessary to monitor it carefully. For this reason, a 33-round planned experiment was carried out for the study of the impact of the machine parameters setup on the topography and morphology of the steel Creusabro 4800. (This material has not yet been the subject of any similar publication.) Metallographic preparations of all samples that allowed the study of subsurface defects using light and electron microscopy were produced. In order to investigate changes in the chemical composition of the surface and subsurface layers of the effects of WEDM machining, a complex chemical composition analysis was performed. A significant effect of the machine parameters setup on the occurrence of subsurface defects was demonstrated and the presence of burned cavities could be completely eliminated with machine parameters setup: gap voltage = 60 V, pulse on time = 8 μs, pulse off time = 40 μs, wire speed = 12 m min −1 and discharge current = 25 A.